Novel advances in the treatment of osteoporosis. - Chan, C; Mason, A; Cooper, C; Dennison, E (Oxford University Press, 2016)
Introduction Osteoporosis is a significant public health issue affecting over half of women aged over 50. With an aging population its importance is set to increase further over time. Prevention of fragility fractures avoids significant mortality and morbidity as well as saving significant direct and indirect costs to the economy. In this review, we discuss existing treatments to contextualise the treatment landscape, and demonstrate how our understanding of bone pathophysiology has led to novel therapies – in the form of combinations and altered durations of existing treatments, as well as newer drug therapies. Sources of data Pubmed and Embase were searched for randomised controlled trials of new therapies for osteoporosis. These searches were supplemented with material presented in abstract form at international meetings Areas of agreement New drugs that appear promising in the treatment of osteoporosis include the cathepsin K inhibitor, monoclonal antibodies against sclerostin, and parathyroid hormone related peptide. Areas of controversy Separate to the development of novel drug therapies is the issue of how best to use agents that are currently available to us; specifically which agent to choose, alone or in combination; duration of therapy; how best to identify patients at highest risk of fracture, and to ensure the highest possible adherence to medication. Many of these issues have been addressed in other excellent review papers, and will not be considered in detail here. Growing points As with all new treatments, we await results of long term use, and experience in ‘real life’ patient populations Areas timely for developing research As alluded to above, data are urgently required regarding the optimal duration of therapy; use of combination therapy; ordering of therapies for best therapeutic effect. As stratified medicine becomes more strongly considered in all areas of therapy, its merits in osteoporosis as in other musculoskeletal conditions, is timely and valuable.